Effect of median nerve neuromobilization on functional status in patients with carpal tunnel syndrome: a double blinded randomized control trial - Ijaz, Muhammad Junaid; Karimi, Hossein; Gillani, Syed Amir; Ahmad, Ashfaq; Chaudhary, Muhammad Asad (Journal of the Pakistan Medical Association, 2022)
Objective: To measure additional benefits of neuromobilisation along with conventional treatment in improving the functional status in patients having carpal tunnel syndrome. Method: The prospective, double-blind randomised controlled trial was conducted from August 2018 to June 2019 at the Physiotherapy outdoor clinic of Mayo Hospital, Lahore, Pakistan, and comprised patients of either gender aged 20-45 years with <3-month history of carpal tunnel syndrome. The patients were randomised into control group 1 and experimental group 2. Group 1 received conservative treatment including ultrasound therapy, wrist splinting, and tendon-gliding exercises, while Group 2 additionally received neuromobilisation. Functional limitation was measured using the Functional Status Scale and the Symptom Severity Scale of the Boston Carpal Tunnel Syndrome Questionnaire. Patients had 2 sessions per week for 6 weeks. Clinical data was noted at baseline, after 3 weeks of treatment and finally at the end of the 6-week intervention. Data was analysed using SPSS 21. Results: Of the 66 patients, there were 33(50%) in Group 1; 3(9.1%) males, 30(90.9%) females, overall mean age 37.79 ±5.91 years. The remaining 33(50%) were in Group 2; 2(6.1%) males, 31(93.9%) females, overall mean age 35.58 ±7.15 years. Both the groups showed significant improvement (p <0.05), but the addition of neuromobilisation in Group 2 showed better results compared to Group 1(p<0.05). Conclusion: The addition of neuromobilisation to routine physical therapy was found to have significantly decreased the symptoms of carpal tunnel syndrome and improved the functional status of the patients. Key Words: Functional status, Carpal tunnel syndrome, Neuromobilisation.